Proteomics-Based Mechanistic Investigation of Escherichia coli Inactivation by Pulsed Electric Field - Liu, Zhenyu; Zhao, Lingying; Zhang, Qin; Huo, Nan; Shi, Xiaojing; Li, Linwei; Jia, Liyan; Lu, Yuanyuan; Peng, Yong; Song, Yanbo (Frontiers in Microbiology, 2019)
The pulsed electric field (PEF) technology has been widely applied to inactivate pathogenic bacteria in food products. Though irreversible pore formation and membrane disruption is considered to be the main contributing factor to PEF’s sterilizing effects, the exact molecular mechanisms remain poorly understood. In this study, by using mass spectrometry-based label-free quantitative proteomic analysis, we compared the protein profiles of PEF-treated and untreated Escherichia coli. We identified a total of 175 differentially expressed proteins, including 52 candidates that were only detected in at least two of the three samples in one experiment group but not in the other group. Functional analysis revealed that the differential proteins were primarily involved in the regulation of cell membrane composition and integrity, stress response, as well as various metabolic processes. The results of the current study offered valuable insight into PEF-induced cell inactivation.